Interprofessional conflict and conflict management in an educational setting. (3rd April 2019) - Broukhim, Michael; Yuen, Francis; McDermott, Haley; Miller, Keri; Merrill, Leslie; Kennedy, Robin; Wilkes, Michael
Abstract: Background : Whenever health professionals work together as a team, conflict is inevitable – some would argue even necessary. However, conflict can have negative effects on patient care, job satisfaction, personal wellness, and professional productivity. Purpose : This study aims to describe interprofessional conflicts in a hospital setting from the perspective of three groups of health science students. Methods: An online questionnaire survey collected data from 225 health science students (medicine, nursing, and social work) in Northern California (USA). Quantitative and qualitative analyses were conducted resulting in seven central themes of conflict. Results: There are differences among health professional students in terms of how conflict is experienced and managed. Nursing students and medical students were more likely to take on the "victim" role when explaining their conflict, and their conflicts were more likely to be intra-professional. The most common cause of conflicts was related to hierarchy and power issues. The majority were dissatisfied with the way the conflict was resolved. Conclusions: Findings from this study can be used to design interprofessional curriculum to improve outcomes from conflicts and improve wellbeing, job satisfaction, and reduce patient turnover.